EDUCATION OF LACTATION PREPARATION IN PREGNANCY FOR THE SUCCESS OF EXCLUSIVE BREASTFEEDING, AT THE HEALTH SERVICE CENTER, JOHAR BARU, CENTRAL JAKARTA - Ida Pratiwi, Agustina; Sri Artina Dewi, Ni Nyoman; Kartiko Kusumo Wardani, Dyah Woro; Suhaid, Dewi Novitasari; Margaretha Manungkalit, Eviyani; Panselina Widowati, Lorensia; Leoni Irawan, Yetty; Suci Dwi Aningsih, Baharika (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Lactation / Breastfeeding is a natural process for a woman, but it is vital to prepare in order to achieve the success of exclusive breastfeeding. Indonesian Health Profile (2018) shows that exclusive breastfeeding coverage in Indonesia is 65.16%, falling short of the target of 80%. Only 42% of the 135 million babies born each year are nursed during the first hour of life, 38% exclusively breastfeed for the first six months, and 58% continue to breastfeed until the age of two. The dearth of information among mothers about exclusive breastfeeding and the absence of assistance from medical professionals in this area are two influential factors. Breast milk is a critical source of nutrition and energy for sick people, and it improves infant development, lowers morbidity and mortality, and lowers the risk of chronic diseases. Breastfeeding also improves the health and happiness of mothers, lowers the incidence of ovarian and breast cancer, and conserves resources for both families and the country (WHO, 2021). The method used in this activity is to educate pregnant women and their families on the value of getting ready for lactation during pregnancy. Following counseling, there was an increase in knowledge about pregnancy-related lactation preparation.